Repeated sprint exercise impairs contractile force of isolated single human muscle fibres - Ortenblad, N.; Hvid, L. G.; Jensen, R.; Andersson, E.; Willis, S. J.; Holmberg, H. C.; Gejl, K. D. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The purpose of the present study was, to examine the effects of repeated sprint skiing on the contractile apparatus of single muscle fibres obtained from a group of elite cross-country (cc) skiers. We have recently demonstrated that prolonged cycling exercise impairs the contractile apparatus of single muscle fibres, and that this can be restored during recovery. However, little is known about the effect of repeated high intensity exercise on single fibre properties, as i.e., during sprint skiing. We hypothesize that repeated high-intensity exercise in highly trained subjects will impair the contractile apparatus maximum force output.